Extending Awareness of Catholic Healthcare Ethics Among Junior Clinicians: A Qualitative Study - O'Callaghan, Clare (Journal of religion and health, 2018)
As Catholic healthcare organizations form a substantive part of healthcare delivery in the USA and Australia, ethical standards for Catholic health care were developed to guide practice. This study examined junior staff's understanding of Catholic ethics. Using a qualitative descriptive design, we recruited 22 medical and nursing staff to interviews/focus groups. Though Catholic ethics seldom informed ethical approaches, the principles were acknowledged as being useful to support development of confident and respectful care approaches. Findings provide early insights into challenges faced in considering implementation of ethical codes across both secular and religious healthcare organizations, suggesting that a more creative and pastoral approach to dialoguing and implementing Catholic ethics is required.